Y, the last man. Vol. 03 One small step - Vaughan, Brian K. (Vaughan, Brian K. Y the last man, 2003)
Yorick Brown, the only human male to survive a global sex-specific plague, may not be unique for much longer. As he makes his way across the remains of America (together with a secret government agent, a cloning specialist, and the only other male mammal to survive, Ampersand the monkey), the last man on Earth is about to have an unexpected visitation from above. Three astronauts are descending from the exhausted International Space Station, and two of them are men.